Liberia : Seventh and Eighth Reviews Under the Extended Credit Facility Arrangement, and Request for Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Liberia's Seventh and Eighth Reviews under the Extended Credit Facility Arrangement, and Request for Waiver of Nonobservance of Performance Criteria (PCs). Three of six structural benchmarks (SBs) for the seventh review and two of four SBs for the eighth review were met. The rest, except one, were met with a delay. Risks are concentrated in the near term. Based on the strength of the authorities' policy commitments and corrective measures, the IMF staff supports the authorities' request for waivers for nonobservance of PCs and supports completion of the seventh and eighth program reviews.